Complications of revision knee arthroplasty - H. V. Haiko; V. M. Pidhaietskyi; O. M. Sulyma; V. M. Chornyi (Zaporožskij Medicinskij Žurnal)
Due to the growing scale of arthroplasty and the widening of indications for knee joint replacement, the durability of joint functioning has become a critical issue. Untimely diagnosis and inadequate treatment of patients with endoprosthesis component loosening leads to major bone defects.